Analysis of Feeder Reliability in a 20 kV Distribution Network System Using the Reliability Network Equivalent Approach (RNEA) Testing Method - Nandy Rizaldy Najib; Hamma (PT FORMOSA CENDEKIA GLOBAL, 2023)
The reliability of the network in energy services in the distribution system can be seen from the frequency of blackouts and the length of time outages occur. The Reliability Network Equivalent Approach (RNEA) method is used to analyze the reliability of a large and complex distribution system into a simple form, with elements of an equivalent approach. From this reliability, the load point reliability index and system reliability index values ​​are obtained. Parang Banoa feeders using the RNEA method in 2021 with a SAIFI value of 4.813 [failure/customer/year] and SAIDI of 12.003 [hours/customer/year], while RRI feeders have a SAIFI value of 1.827 [failure/customer/year and SAIDI of 4,619 [hours/customers/year]. Based on the calculation results, the Parang Banoa feeder is categorized as unreliable because its value exceeds the 1986 SPLN 68-2 standard, while the RRI feeder is said to be reliable because its value is below the 1986 SPLN 68-2 standard.